MOTIVASI SISWA DALAM PEMBELAJARAN SENI TARI DI SMP NEGERI 1 LUBUK BASUNG KABUPATEN AGAM - Lidia Triana; Idawati Syarif; Susmiarti Susmiarti (SENDRATASIK UNP, 2013)
Abstract This study aims to identify and describe the student motivation in learning dance at SMP Negeri 1 Lubuk Basung Agam Regency. This is descriptive quantitative research. Object of this study is the students in learning dance in grade VIII SMP Negeri 1 Lubuk Basung Agam Regency. Primary data of the research were collected through questionnaires. The population of this study was grade VIII SMP Negeri 1 Lubuk Basung Agam Recency which consists of 5 (five) classes totally 152 students. Based on analysis indicated that students' motivation in learning dance seen from the intrinsic motivation of the students was very good 94.93% (discipline 90.22%, responsibility 96.75%, and participation 97.82%). Similarly, extrinsic motivation of the students was also very good 89.12% (facilities 90.06% , infrastructure 80.23%, and awards 97.08% ).